The THE AUTHORITY OF WOMEN SCHOLARS IN THE TAKLIM COUNCIL - Zaen, Nihayatus; Hulwana, Rifqi Qonita (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2025)
This research focuses on the role and religious authority of female muslim scholar of pesantren by examining a study of the Majelis As-Sholihat Situbondo during the period of 1990-2005, under the leadership of Nyai Zainiyah As’ad. This study employs a descriptive qualitative approach to reveal the profile of Nyai Zainiyah As’ad, the process of establishment and development of the Majelis Taklim As-Sholihat, as well as the construction of religious scholarly authority cultivated within that space. The research findings indicate that the agency of female ulama can be formed not only through resistance to religious and cultural norms but also through the strengthening of existing traditional values. Although Nyai Zainiyah’s struggle did not explicitly promote a feminist or gender equality agenda, her role demonstrated the capacity of women to lead and empower female communities through dakwah activities. This Majelis Taklim acted as more than merely a religious education forum; it functioned as a transformative public space that reinforced intellectual and spiritual capacities. Through this study, an understanding is gained that the theology of women developed in the majelis taklim can serve as a vital instrument for strengthening religious identity while simultaneously encouraging progressive and contextual social change grounded in Islamic values.